Advances in the Use of Nanocomposite Membranes for Carbon Capture Operations - Emmanuel E. Okoro; Rachael Josephs; Samuel E. Sanni; Yuven Nchila (International Journal of Chemical Engineering)
The adoption of nanodoped membranes in the areas of gas stream separation, water, and wastewater treatments due to the physical and operational advantages of such membranes has significantly increased. The literature has shown that the surface structure and physicochemical properties of nanodoped membranes contribute significantly to the interaction and rejection characteristics when compared to bare membranes. This study reviews the recent developments on nanodoped membranes, and their hybrids for carbon capture and gas separation operations. Features such as the nanoparticles/materials and hybrids used for membrane doping and the effect of physicochemical properties and water vapour in nanodoped membrane performance for carbon capture are discussed. The highlights of this review show that nanodoped membrane is a facile modification technique which improves the membrane performance in most cases and holds a great potential for carbon capture. Membrane module design and material, thickness, structure, and configuration were identified as key factors that contribute directly, to nanodoped membrane performance. This study also affirms that the three core parameters satisfied before turning a microporous material into a membrane are as follows: high permeability and selectivity, ease of fabrication, and robust structure. From the findings, it is also observed that the application of smart models and knowledge-based systems have not been extensively studied in nanoparticle-/material-doped membranes. More studies are encouraged because technical improvements are needed in order to achieve high performance of carbon capture using nanodoped membranes, as well as improving their durability, permeability, and selectivity of the membrane.